Implikasi Teori Humanistik Abraham Maslow dalam Pembelajaran Pendidikan Agama Islam - Muhammad Al Fatih (Gemi: Jurnal Penelitian dan Pengabdian, 2026)
Currently, many educational institutions place greater emphasis on the cognitive aspects of the learning process, while human dimensions such as students' emotional and social needs are often neglected. This approach can negatively impact students' mental development. This article discusses the application of Abraham Maslow's theory in the context of Islamic religious education as a more holistic alternative. Maslow's theory, which emphasizes the importance of fulfilling basic needs through to self-actualization, can serve as the foundation for a humanistic approach to the learning process. Using qualitative methods based on a literature review, this article concludes that teachers should act as flexible, creative, and empathetic facilitators. Active and enjoyable learning enables students to integrate religious values into their daily lives. This approach aims to shape individuals who are not only intellectually intelligent but also emotionally and spiritually mature, enabling them to reach their full potential.